O conceito de niilismo na obra de Friedrich Nietzsche - Soares, Breno Dutra Serafim (2014)
The question that motivated this thesis was formulated as follows : what is nihilism in the works of Friedrich Nietzsche? Before entering the study of Nietzsche's work, we developed a foreshortened history on the subject. The second chapter is devoted to works published by Nietzsche in life. We look at how, since these works, the theme appears, initially, incipiently, without the designation that would receive; but later, under the nomenclature which would be adopted in posthumous writings. We see how nihilism is connected to the collapse of metaphysics, religion and morality. In the third and final part, we discuss about nihilism as expounded in the posthumous fragments. We try to give a thread to ideas that are scattered throughout fragments dating from 1885 to 1889. We have the opportunity to see how Nietzsche elaborates a more robust conceptualization of the theme by establishing distinctions such as active and passive nihilism, as well as stages in which the consciousness of nihilism worsens.